The influence of surface properties on colour centres in diamond - Anja Sadzak; Anke Krueger (Materials for Quantum Technology)
Colour centres in diamonds have attracted considerable interest for quantum sensing applications. Boasting great photostability, long coherence times at room temperature and unique electronic properties that allow for optical initialization and readout of their quantum state, colour centres have found use in a variety of techniques for thermometry, magnetometry and nanoscale spectroscopy. Coupled with the possibility of preparing nanoparticles, their excellent biocompatibility and versatile surface chemistry that allows for functionalization and fine-tuning of surface properties, diamonds hosting colour centres have proven to be a versatile and flexible platform for measurements of local properties in a wide range of biological and biochemical systems. In this perspective, we summarize the key properties of the colour centres in diamonds and how different surface chemistry impacts their electronic properties. Finally, we discuss the crucial role of surface chemistry in various sensing applications and highlight the potential of diamond materials to address current challenges in quantum science and technology.